2020
DOI: 10.1103/physrevresearch.2.013095
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing open quantum batteries by sequential measurements

Abstract: A quantum battery is a work reservoir that stores energy in quantum degrees of freedom. When immersed in an environment an open quantum battery needs to be stabilized against free energy leakage into the environment. For this purpose we here propose a simple protocol that relies on projective measurement and obeys a secondlaw like inequality for the battery entropy production rate. PACS numbers: 03.65. Yz, 05.70.Ln, 42.50.Lc Among recent research in quantum thermodynamics [1][2][3][4][5], the design of quan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(57 citation statements)
references
References 54 publications
0
57
0
Order By: Relevance
“…The transfer of energy from one spatial location to another has always been a central topic in physics. Recently, a lot of attention has been devoted to the so-called quantum batteries, i.e., quantum devices able to store energy and release it upon demand at specific times [34,35,36,37]. Devising a protocol to extract the maximum amount of energy from a charged battery, establishing a bound on its amount, and stabilizing the battery's charge has been addressed in several works [38,39,40,41,42] Another line of research is embodied by the investigation of the charging protocol a quantum battery [43,44,45], and, apart from a few instances [46], mainly non-interacting systems embodying the quantum battery have been considered.…”
Section: Energy Transportmentioning
confidence: 99%
“…The transfer of energy from one spatial location to another has always been a central topic in physics. Recently, a lot of attention has been devoted to the so-called quantum batteries, i.e., quantum devices able to store energy and release it upon demand at specific times [34,35,36,37]. Devising a protocol to extract the maximum amount of energy from a charged battery, establishing a bound on its amount, and stabilizing the battery's charge has been addressed in several works [38,39,40,41,42] Another line of research is embodied by the investigation of the charging protocol a quantum battery [43,44,45], and, apart from a few instances [46], mainly non-interacting systems embodying the quantum battery have been considered.…”
Section: Energy Transportmentioning
confidence: 99%
“…This setup presents a number of benefits, not simultaneously met in any other battery-charger setup, such as no need of fine control over the preparation of the charged state and no necessity to exert any effort to maintain the battery in that state. Indeed, the existing setups either require isolating the system or engineering a 033413-9 special system-bath evolution [9,11,12] or maintaining fragile internal symmetries [13,14] or active external stabilization [16] to preserve the charged state.…”
Section: Discussionmentioning
confidence: 99%
“…II and Appendix B), our device offers two main advantages: (i) the creation of the battery's charged state requires no fine external control and, since thermalization is the process preparing that state, is robust against minor variations of the system-bath interaction; (ii) it costs nothing to maintain the charged state for as long as might be needed-it is the stationary state of system-bath interaction. These advantages are not simultaneously met in other battery designs which either require finely tuned external fields to perform unitary charging operations on the depleted state of the battery and assume that the battery is isolated after it is charged [11,12]; or require system-bath interaction engineering [9]; or, to prevent the battery from leaking the charge, either rely on fragile symmetries of the system-bath interaction [13,14] or actively manipulate the battery [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…However, the coupling between the charger and its external power supply necessarily introduces noise, which limits the charging process [36]. Recent proposals have shown how to mitigate the effect of environmental noise via measurements [37] or dark states [38,39], while other authors have instead suggested to harness noise as a charging mechanism [40][41][42][43][44][45]. These approaches are notable due to their stability, meaning that the battery's charge tends to a stationary value instead of oscillating over time [38,46].…”
Section: Introductionmentioning
confidence: 99%